Boundary cap neural crest stem cell transplants contribute Mts1/S100A4-expressing cells in the glial scar. (June 2017) - Trolle, Carl; Ivert, Patrik; Hoeber, Jan; Rocamonde-Lago, Iris; Vasylovska, Svitlana; Lukanidin, Eugen; Kozlova, Elena N
Aim: During development, boundary cap neural crest stem cells (bNCSCs) assist sensory axon growth into the spinal cord. Here we repositioned them to test if they assist regeneration of sensory axons in adult mice after dorsal root avulsion injury.Materials & methods: Avulsed mice received bNCSC or human neural progenitor (hNP) cell transplants and their contributions to glial scar formation and sensory axon regeneration were analyzed with immunohistochemistry and transganglionic tracing.Results: hNPs and bNCSCs form similar gaps in the glial scar, but unlike hNPs, bNCSCs contribute Mts1/S100A4 (calcium-binding protein) expression to the scar and do not assist sensory axon regeneration.Conclusion: bNCSC transplants contribute nonpermissive Mts1/S100A4-expressing cells to the glial scar after dorsal root avulsion.